Dimensions of Rural-to-Urban Migration and Premarital Pregnancy in Kenya. Issue 1 (July 2013) - Xu, Hongwei; Mberu, Blessing U.; Goldberg, Rachel E.; Luke, Nancy
Rural-to-urban migration is increasingly common among youths in developing countries and could affect sexual activities with consequences for premarital pregnancies. We use life history data collected in Kisumu, Kenya, to investigate how the timing and number of rural-to-urban moves are associated with premarital pregnancy. Among sexually experienced young women aged 18 to 24 ( N = 226), 60 percent had moved at least once in the past 10 years and 38 percent had experienced a premarital pregnancy. Results of the event history analysis show that those who experienced one or two moves were at increased risk for premarital pregnancy compared to nonmovers. Also at increased risk were movers whose most recent move occurred in the past 7 to 12 months. Finally, those whose last move occurred at age 13 or younger were also at an elevated risk. Migration brings about specific risks and needs for youths, including the need for sexual and reproductive health education and services, which should be made available and accessible to new urban residents.